E não viveram felizes para sempre: A vulnerabilidade emergente do divórcio e seus efeitos sobre o comportamento de consumo para a criança em famílias monoparentais femininas. - Souza, Andressa Sullamyta Pessoa de (2016)
The present study aimed to characterize the vulnerability experiences lived in consumer relations directed to the children of female single parents. In order to do so, the main theoretical aspects related to the discipline of marketing and society, consumer vulnerability, contemporary families and consumption, and divorce and its effect on household consumption were addressed. The combination of those theoretical aspects shaped the conceptual research model. The methodological decisions focused on the representation of a qualitative approach, made possible by individual semi-structured face-to-face interviews conducted with audio recording. In total, fifteen divorced mothers of children up to twelve years or children older than twelve, but that at the time of divorce found themselves in that particular age has been conveniently invited and interviewed in 2015, in places previously established according to their preferences. The transcript of the interviews and the content analysis technique presented therefore three categories for assessment, which aimed, respectively, to recognize the general aspects of the divorce process and the characteristics of the nuclear family consumption versus the consumption of female single-parent family, and also to characterize the vulnerability exploited in context. The results indicate that the vulnerability in this context is due to: reduction of paternal involvement in family income, the consumption deprivation caused by the new financial conditions of the mother, the conflicts between the former spouses and family, and the characteristics and individual states such as competion, materialism, anger, jealousy and shame caused by the dependence on third parties.